Beispiel Nr: 27
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(3/0)\qquad Q(4/0) \\\\ \\ \textbf{Rechnung:} \\ P(3/0)\qquad Q(4/0) \qquad a=0 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=0(x-3)(x-4)\\ y=0(x^2- x \cdot 4 -3\cdot x +3\cdot 4 )\\ y=0(x^2 -7 x+12) \\ y= 0 $